Are all aspects of lean production bad for workers? An analysis of how problem‐solving demands affect employee well‐being. (13th August 2018) - Huo, Meng‐Long; Boxall, Peter
Abstract: This study is concerned with the debate around employee well‐being in the environment of lean production. It applies the job demands–resources model to examine the effects of problem‐solving demands and job resources (training, participation in decision‐making, and line manager support) on employee engagement and exhaustion in a Chinese manufacturer. It examines previously untested interactions and shows that these job resources created a "buffering effect" in the relationship between problem‐solving demands and exhaustion. It also shows a "coping effect" because the relationship between resources and engagement was strengthened as problem‐solving demands increased. Rather than being uniformly positive or negative, the results suggest that the overall impact of lean production on worker well‐being is likely to depend on the ways in which managers create scope for worker involvement in decision‐making, target resources to the specific job demands, and adjust resource levels to the degree of these demands.